Hydrocarbon Oxidation by a Porphyrin-π-Cation Radical Complex - Mc Donald, Aidan (My University, 2023)
Heme and chlorin π-cation radical oxidants are widely implicated in biological and synthetic oxidation catalysis. Little insight into the role of π-cation radicals in proton coupled electron transfer (PCET) oxidation is available. We prepared a NiII-porphyrin-π-cation complex ([NiII(P⋅+)]) and found it to be capable of the oxidation of a variety of simple hydrocarbon substrates. Interestingly, some of the products were hydroxylated, with ([NiII(P⋅+)]) working in concert with atmospheric O2 to yield hydroxylated hydrocarbons. Kinetic data suggested that the porphyrin-π-cation radical species oxidised substrates through a concerted PCET mechanism, where the porphyrin-π-cation radical accepted the electron, and the proton was transferred to a free anion. Our findings highlight the potential role of π-cation radicals as hydrocarbon activators, demonstrating that porphyrin ligand non-innocence could be a readily manipulated resource for oxidation catalyst development.
PUBLISHED
Keywords: Heme and chlorin π-cation radical oxidants; hydrocarbon substrates; oxidation catalyst development